2014
DOI: 10.1117/1.jbo.19.8.087002
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Raman spectroscopic investigations on hemoglobin ordering in red blood cells

Abstract: We have investigated the dependence of the Raman spectrum of an optically trapped red blood cell (RBC) on the orientation of the cell, relative to the polarization direction of the Raman excitation beam. The Raman scattered light polarized parallel to the polarization direction of the excitation beam was observed to depend upon the orientation of the cell. In particular, the heme bands at ∼754 cm⁻¹ and in the 1500 to 1700 cm⁻¹ region were observed to become maximum when the cells' equatorial plane was parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Here we briefly summarise common phantoms used for biomedical polarimetric techniques. These techniques include polarised wide-field microscopy 16 , 24 , 183 , polarised light spatial frequency imaging 184 , polarimetric endoscopy 185 190 , spectral light scattering polarimetry 18 , 82 , 191 193 , polarised fluorescence spectroscopy 194 196 , polarised confocal microscopy 197 , polarised Raman-spectroscopy 198 , 199 , polarised super-resolution microscopy 154 , 155 , polarisation sensitive optical coherence tomography 200 218 , non-diffraction beam polarimetry (such as Bessel beam based) 219 , polarisation-resolved nonlinear microscopy (including second/third harmonic generation) 220 226 , and polarised speckle imaging 213 , 227 (several techniques will be mentioned again in the Discussion). The relationship between incoherence and depolarisation of the light should be kept in mind when considering coherence based polarimetric techniques: they are different but related optical concepts.…”
Section: Vectorial Information Analysis For Biomedical Applicationsmentioning
confidence: 99%
“…Here we briefly summarise common phantoms used for biomedical polarimetric techniques. These techniques include polarised wide-field microscopy 16 , 24 , 183 , polarised light spatial frequency imaging 184 , polarimetric endoscopy 185 190 , spectral light scattering polarimetry 18 , 82 , 191 193 , polarised fluorescence spectroscopy 194 196 , polarised confocal microscopy 197 , polarised Raman-spectroscopy 198 , 199 , polarised super-resolution microscopy 154 , 155 , polarisation sensitive optical coherence tomography 200 218 , non-diffraction beam polarimetry (such as Bessel beam based) 219 , polarisation-resolved nonlinear microscopy (including second/third harmonic generation) 220 226 , and polarised speckle imaging 213 , 227 (several techniques will be mentioned again in the Discussion). The relationship between incoherence and depolarisation of the light should be kept in mind when considering coherence based polarimetric techniques: they are different but related optical concepts.…”
Section: Vectorial Information Analysis For Biomedical Applicationsmentioning
confidence: 99%
“…The results of theoretical simulations suggested that hemoglobin ''must be present in an ordered arrangement, such that the hemeporphyrin planes are preferentially orientated parallel to the RBCs' equatorial plane''. 59 Laser tweezers Raman spectroscopy has become an increasingly important technique in the study of living RBCs, for investigations of oxygenation within single cells, [60][61][62] and for investigation of the effects of laser light on RBC biology. [63][64][65] The method has also been integral for characterizing red cell response to stimulus/ stress (e.g., alcohol-induced denaturation, 66 electrical current, 67 oxidative stress, 68 and pH changes 69 ), and has been deployed to compare oxygen uptake of different globin-containing cells.…”
mentioning
confidence: 99%
“…Based on theoretical results in Ref. [39] hemoglobin exists in an ordered arrangement, such that the heme-porphyrin planes are preferentially orientated parallel to the RBCs' equatorial plane. The glycation of red blood cells can be precisely estimated using the electric/dielectric losses and polarization changes, described in detail in Ref.…”
Section: Resultsmentioning
confidence: 99%